Student Evaluations of College Professors: Identifying Sources of Bias - Cramer, Kenneth M.; Alexitch, Louise R. (Canadian Journal of Higher Education, 2000)
Previous studies have found that students’ evaluations of their professors’ teaching ability may be affected by such factors as students’ expectations and gender stereotypes. The present study examined how students’ evaluation of faculty may be affected by student’s gender, professor’s gender, discipline, and a variety of demographic and social variables. Undergraduate students (N = 910) evaluated one of their professors on sensitivity to students’ needs, quality of teaching, course structure, and treatment of designated group members (e.g., visible minorities). Results showed that female students rated their professor higher on sensitivity to students’ needs and treatment of designated groups than male students. Science students rated their professor lower on teaching quality and treatment of designated groups than either Social Science or Fine Arts/Humanities students. In addition, students’ ratings correlated with how often a professor met with students outside of class, when the class was scheduled, and class size. The implications for using student evaluations to accurately assess professors’ teaching ability are discussed.